2015
DOI: 10.4103/0253-7176.168564
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms at Onset in First Episode Schizophrenia: Caregivers Perspectives

Abstract: Background:Early recognition of symptoms is important in the management of psychosis. Caregivers understanding and attribution of symptoms plays a major role in treatment selection.Aim:The aim was to identify the various symptoms cluster recognized by caregivers at illness onset in first episode schizophrenia.Subjects and Methods:In a cross-sectional study 40 key caregivers of patients with first episode of Schizophrenia (International Classification of Diseases-10) attending the outpatient services of Schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…High tolerance for behavioral abnormality and disability in Asian families often leads to symptoms being unrecognized (38). Misattribution of illness behaviors to typical adolescence, stress, lifestyle or supernatural causes, which was also observed in this current study, is another common cultural contribution to delay in help-seeking (39,40). In Malaysia, beliefs about causes of schizophrenia vary.…”
Section: Discussionsupporting
confidence: 62%
“…High tolerance for behavioral abnormality and disability in Asian families often leads to symptoms being unrecognized (38). Misattribution of illness behaviors to typical adolescence, stress, lifestyle or supernatural causes, which was also observed in this current study, is another common cultural contribution to delay in help-seeking (39,40). In Malaysia, beliefs about causes of schizophrenia vary.…”
Section: Discussionsupporting
confidence: 62%
“…Using Principal Component (PCP) analysis, it was identified that four factors were easily recognised by the caregivers namely, depressive, anxious, irritable, and vegetative factor. 34 Another study examined the expressed emotion in caregivers of individuals with first-episode psychosis shaped by stress and social support to them. The results indicated that caregivers experienced high level of perceived stress, expressed emotion and poor social support.…”
Section: Caregiver Burdenmentioning
confidence: 99%